Deepwater sedimentation and Cenozoic deformation in the Southern New Caledonia Trough (Northern Zealandia, SW Pacific). (April 2018) - Etienne, S.; Collot, J.; Sutherland, R.; Patriat, M.; Bache, F.; Rouillard, P.; Henrys, S.; Barker, D.; Juan, C.
Abstract: The New Caledonia Trough (NCT) is a 2000–3000 m deep bathymetric feature that extends 2500 km from Taranaki, New Zealand, to the western margin of New Caledonia (Northern Zealandia, SW Pacific). The underlying sedimentary basin originates from Cretaceous extension, but underwent a significant Eocene tectonic event that shaped its present physiography. We present an analysis of the basin based on multibeam data, seismic profiles and rock samples collected on the TAN1312 and TAN1409 Expeditions onboard R/V Tangaroa, combined with legacy data. We focus on the southern part of the basin, where new data reveal a link between compressive deformation of Paleocene strata and their potential reworking into the basin. On the western basin side, Upper Cretaceous to Paleocene strata were deformed by local reverse faults and folds that created a sub-circular bathymetric ridge and seabed exposure. This folded unit (seismic Unit 2) is sharply overlain by a restricted interval imaged as chaotic high-amplitude reflections that are interpreted as syntectonic mass-transport deposits due to slope oversteepening (seismic Unit 1b). This unit is stratigraphically below the main basin onlap surface and seismic mapping revealed that it rapidly thins away from the mouth of a present day submarine canyon imaged on the western slope of the basin, and that is diverted by exposures of Unit 2 deformed strata. Deformed and syntectonic intervals are in turn overlain by a flat-lying unit (seismic Unit 1a) we interpret as reflecting a passive basin fill. Our new data provide insight into an extensive deep-water basin that is remote from terrigenous sediment sources, and new constraints on its Cenozoic tectonic history. Stratigraphic ages are constrained by seismic ties to Taranaki basin petroleum wells and biostratigraphic dating of dredged samples. This specific site has particular significance for understanding tectonic events in the southwest Pacific. Indeed, our observations show that deformation is younger than the Paleocene and is envisaged to be a local expression of a widespread Cenozoic compressive event (called "TECTA", Tectonic Event of the Cenozoic in the Tasman Area), which affected the region after the Mesozoic rifting. On a regional perspective, this study provides new insights on the evolution of the submerged Zealandia continent and associated geodynamic processes such as Gondwana break-up and initiation of the Tonga-Kermadec subduction. Highlights: We present a surface and seismic analysis of the Southern New Caledonia Trough. Basin margins show Cenozoic compressive features and mass transport deposits. A prominent present-day submarine canyon is possibly inherited from this event.